Asymmetrical relationship between oil prices, gold prices, exchange rate, and stock prices during global financial crisis 2008: Evidence from Pakistan - Umaid A. Sheikh; Muzaffar Asad; Zahid Ahmed; Umer Mukhtar (Cogent Economics & Finance, 2020)
The study investigated that whether the relationship between macroeconomic fluctuations and stock indexes is symmetrical or asymmetrical in nature. This study employed nonlinear autoregressive distributed lag models for the times before and after 2008 economic crises. The overall sample period contains 168 observations between January 2004 and December 2018. The period between January 2004 and December 2007 was considered as pre-economic crisis period containing 48 observations whereas, period between January 2008 and December 2018 was considered as post-economic crisis containing 120 observations. Four different types of unit root tests, i.e., augmented Dickey Fuller test, Philips Perron test, Zivot-Andrew unit root, and Kwiatkowski Philips Schmidt Shin test have been employed to find out the stationarity in data. Findings suggested that in the long run and before global financial crisis, investors react differently to gold prices and oil prices. In long run and after crisis, investors have shown different reactions to all macroeconomic fluctuations. This showed that after crisis, investors reacted differently to positive and negative shocks of gold prices, exchange rate, and interest rate. Another interesting aspect that after global financial crisis, investors reacted only to positive shocks of gold prices, interest rates, and exchange rate in long run. This research contributes to existing literature by identifying that relationship between macroeconomic fluctuation and stock prices is asymmetric in nature whereas, in previous researches authors have assumed linearity in the time series data. The asymmetric effect of macroeconomic variables on stock prices should be considered for investors, governments, and other stakeholders during investment decisions.
Keywords: 330; Asymmetrical; nonlinear autoregressive distributive lag model; macroeconomicvariables and stock prices; stock prices; global financial crisis